PTSD and Opioid Use: Challenges Facing Veterans of Iraq and Afghanistan Wars - Mundt, Laura Elizabeth (East Carolina University, 2021)
The Opioid Crisis is a national problem caused in large part by the high rate of prescribing or misuse of prescription pain medications. Health care providers are prescribing opioids at high rates to wounded veterans to treat their pain. Post-Traumatic Stress Disorder (PTSD) is a common diagnosis among war veterans and makes such veterans potentially vulnerable to opioid use and misuse. Data indicate that veterans with PTSD are more likely to develop an opioid use disorder than veterans who did not have a prior PTSD diagnosis. For these reasons, the goals of this honors project were to: a) explore select issues about the opioid crisis in this country, and b) to explore the impact PTSD, and opioid use and its addictive nature can have on veterans of the Iraq and Afghanistan wars. Emphasis was placed on those veterans with co-occurring PTSD. This honors project has both a scholarly and a creative focus: an evidence-based critical review paper synthesizing data from the literature, and two major works of original representational art. Methods included a focused PubMed search to identify the select data-based articles for relevance and inclusion. The scholarly review consisted of 21 quantitative and qualitative evidence-based publications. A matrix model, and a narrative review served to guide the review process. The qualitative data provided a deeper understanding of the veterans’ human experiences when dealing with PTSD, and co-occurring PTSD and opioid use or opioid use disorder. The student kept an ongoing record of recurring themes and powerful images that emerged from the veterans’ stories found in the qualitative studies. These themes and images are discussed in the paper, and served to inspire her original representational paintings of the veterans’ experiences. This honors project offers an overview of select issues about the opioid crisis as well as a window into the lived experiences of veterans from the Iraq and Afghanistan wars challenged by PTSD and opioid use or opioid use disorder. The scholarly paper and the veterans’ stories in artform offer nurses and other health care providers knowledge and insights into how they can more effectively and compassionately assess and provide care to veterans facing these challenges.
Keywords: PTSD; Opioid; Veteran